2017
DOI: 10.3390/ijms18071407
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Effects of Saponins from Leaves of Panax quinquefolius against Cisplatin-Induced Acute Kidney Injury

Abstract: Abstract:Although cisplatin is an anticancer drug that has activity against malignant tumor, it often causes nephrotoxicity. Previous reports have confirmed that the saponins from the leaves of P. quinquefolium (PQS) exerted many pharmacological activities. However, the renoprotective effects of PQS were still unknown. The purpose of the present research was to discuss renoprotective effect of PQS in a mouse model of cisplatin-induced acute kidney injury (AKI). The levels of blood urea nitrogen (BUN) and serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 61 publications
5
50
0
Order By: Relevance
“…Caspases have major roles in initiating degradation phases of apoptosis (Uğuz et al, ). Therefore, the current results confirmed the apoptosis and caspase data related to DTX (Gan et al, ; Hussein et al, ; Ma et al, ). However, we showed cell‐specific protective role of MEL and Se on the apoptosis level and caspase activation in the normal kidney and testes of DTX group.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Caspases have major roles in initiating degradation phases of apoptosis (Uğuz et al, ). Therefore, the current results confirmed the apoptosis and caspase data related to DTX (Gan et al, ; Hussein et al, ; Ma et al, ). However, we showed cell‐specific protective role of MEL and Se on the apoptosis level and caspase activation in the normal kidney and testes of DTX group.…”
Section: Discussionsupporting
confidence: 89%
“…Cellular stress induces stimulation of intrinsic apoptotic pathway and, in turn, activates several protein families including the Bcl‐2 family. When Bcl‐2 is activated by cellular oxidative stress, casp‐9 is directly cleaved, resulting in other caspase activation including casp‐3 (Kahya et al, ; Ma et al, ). After observation of increased oxidative stress and apoptosis levels in kidneys and testes, we examined the potential protective effects of MEL and Se on the caspase changes in the DTX‐induced kidney and testes oxidative toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study revealed that caspase-9 level was induced in cis-treated mice. These results are in agreement with other studies 67,68 . A previous study reported that apoptotic cell death in renal tubule cell was caused by cis through the generation of reactive oxygen species, which activate the pro-apoptotic Bcl-2 family member Bax, which as a consequence induces mitochondrial permeability transition, causing the release of cytochrome c, caspase-9 activation, and entry into the apoptosis execution phase 69 .…”
supporting
confidence: 94%
“…Renal oxidative stress, apoptosis and inflammation have been considered as potential mechanisms underlying nephrotoxicity caused after cisplatin exposure (Ma et al, 2017) . In most cases, cisplatin appears in the plasma and passes through renal tubular epithelial cells, to activate numerous pro-inflammatory cytokines, such as TNF-α, IL-1β, and to induce the generation of the inflammatory mediators iNOS and COX-2 (Honma et al, 2013;Ma et al, 2015) .…”
Section: Introductionmentioning
confidence: 99%